Protecting Intellectual Property and Appropriating Value from Innovations in Weak Appropriability Regimes: Two constructs, barrier to imitation and barrier to commercialization, are two tools multinational enterprises can use to block imitators. Issue 4 (16th May 2021) - Nebus, James; Chai, Kah-Hin; Subramanian, Annapoornima M.
Abstract : Overview: How can multinational enterprises (MNEs) protect their intellectual property (IP) when patents are weakly enforced? An imitator will only take action to appropriate an innovator's value if the imitator has the financial motivation, opportunity, and ability to copy and commercialize the innovator's product/service. If the innovator can decrease one of these conditions to a level that demotivates or inhibits the imitator from taking action, the innovator will have protected its IP. In this article, we introduce the constructs of barrier to imitation and barrier to commercialization, two separate hurdles that can block imitators from appropriating MNE rents. We prescribe MNE IP strategies contingent on country characteristics, local imitator capabilities, an MNE's barriers to imitation and commercialization, and the value chain activities the MNE desires to locate in the country of interest.